Dietary diversity and its associated factors among school children in conflict affected communities of southern Ethiopia - Yakob, Tagese; Israel, Eskinder; Yakob, Begidu; Meshesha, Mekdes; Jambo, Endale; Utalo, Tadewos; Abraham, Awoke (Frontiers in Nutrition, 2025)
BackgroundGlobally, more than 815 million estimated people worldwide suffer from malnutrition or are unable to access enough food due to malnutrition. Conflict remains the single most fundamental factor contributing to chronic malnutrition in the conflict-affected areas. Developing a healthy and balanced dietary pattern is essential for school children because their habits in this period may last longer. Therefore, the current study aimed to assess dietary adequacy level and factors associated among school children in conflicts affected communities of southern Ethiopia.Method and materialsA community-based cross-sectional study was conducted among 616 schoolchildren aged 6 to 12 years with their caregivers using a multistage sampling method. The data were collected by using a structured questionnaire. The data were collected and entered into Epi-data version 4.6.0.2 and exported to STATA software version 14 for analysis. Adequate dietary diversity was defined as the consumption of at least five food groups. Both bivariable and multivariable binary logistic regression were performed. A p-value less than 0.05 on multivariate logistic regression indicated a statistically significant association.ResultsThe overall response rate of this study was 98.5%. The median [inter quartile range (IQR)] dietary diversity score of the studies was 4(3–5) with the prevalence of inadequate dietary diversity among the school children of current study was 59.4% (95% CI, 55.17–62.99). In this study, schoolchildren with no near-health care facility (AOR = 1.95, 95% CI; 1.35–2.82), a family size greater than five (AOR = 1.44, 95% CI; 1.01–2.05), and the absence of a family home garden (AOR = 1.55, CI: 1.35–1.83) were significantly associated with low dietary diversity in school children.ConclusionWhen compared with other studies, dietary diversity in the current study area was low. This emphasizes the need to encourage mothers to use family planning and implementing focused public health interventions, such school lunch programs and community gardening projects, to improve children’s nutritional outcomes and dietary diversity.